Tajikistan Country Economic Memorandum : Nurturing Tajikistan’s Growth Potential - World Bank Group (World Bank, Washington, DC, 2019)
This Country Economic Memorandum (CEM) analyzes a set of the critical constraints to domestic private sector-led and outward-oriented growth in Tajikistan, by examining the structural bottlenecks to private sector investment and exports. The report is selective in looking at key public policies needed to improve Tajikistan’s macroeconomic resilience and foster private sector development to ensure sustainable growth. This CEM should be seen as the first of a series of programmatic work intended to provide advisory support to the Tajik authorities over the medium-term as they update the National Development Strategy. The report focuses on two important areas of public policy: first, the role of the tax system in encouraging investment and entrepreneurship, examines the principal deficiencies in the tax regime and in its administration, and proposes reforms to improve the incentives for investment. Second, in view of the dominance of the state and of state-owned enterprises in the economy and regulatory gaps to ensure level playing field, the report analyzes the competition policy framework, with the aim of identifying policy reforms that will encourage firm entry and create a competitive market in goods and services. The two interrelated objectives – macroeconomic incentives for investment and savings and the domestic competition and tax regime - reinforce each other. The choice of the above thematic areas is guided by the team’s preliminary discussions with various stakeholders within the government and outside the government. The CEM builds on the World Bank’s previous reports on Tajikistan, namely on the Jobs Diagnostics and Systematic Country Diagnostics. The Jobs Diagnostics proposes the government to consider a jobs strategy based on the following three pillars: i) facilitate the creation of more jobs, particularly in the formal private sector; ii) improve the quality of existing jobs, especially in the informal sector; and iii) facilitate better access to jobs including transitions from inactivity to employment and from low to higher quality jobs, with a focus on vulnerable workers. The focus of the CEM is well aligned also with the new Country Partnership Framework (CPF) for 2019-23 currently in making. This report will be followed by analytical and policy work on other critical constraints to private sector-led growth: the establishment of a rules-based policy setting and creating market-supporting institutions that promote greater economic formalization; building upon areas of high potential for transformative change such as the financial strengths of the energy sector and macro-fiscal implications of investments to Rogun HPP; gains from deeper international integration and infrastructure access provided by the Belt and Road Initiative (BRI); and investing in human capital. This chapter of the CEM analyses the main causes of macro-fiscal vulnerabilities and suggests policy recommendations to improve resilience of the Tajik economy.